Through the gender looking-glass: Brazilian tourism entrepreneurs - Costa, Carlos (2021)
This paper aims to investigate the ways in which gender influences entrepreneurial motivations and barriers in the Brazilian tourism sector. As an economic process, tourism entrepreneurship is widely spread in Brazil, with tourism development programs promoting it as a strategy to empower women, however limited research exists on how gender roles influence entrepreneurial ideals. This nationwide study aims to provide a contemporary insight into how tourism entrepreneurs in Brazil are situated within current entrepreneurship theorizing by questioning the complexity caused as gender roles influence entrepreneurial conceptualizations of what constitute motivations and barriers.